(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Metal nanoparticles with a diameter of less than 100 nm have had a significant influence on a variety of biological applications throughout the past several decades. In this article, the eco-friend method of preparing silver nanoparticles (Ag-NPs) utilizing Lactuca sativa leaves extract as a stabilizer and AgSO4 salt as a precursor is described. The Ag-NPs are then used as antibacterial agents. The product’s characteristics were assessed using UV spectroscopy, FE-SEM, TEM, and XRD. Ag-NPs’ size was determined by UV-vis analysis to be 13.7 nm. An analysis using X-ray diffraction (XRD) revealed that the silver nanoparticles had a size of 34 nm. Different sizes, shapes of silver nanoparticles were revealed by FE-SEM images. Additionally, utilizing the agar-well diffusion method, the antibacterial properties of Ag NPs nanoparticles at 100 and 200 μg/mL concentrations were evaluated against a variety of harmful bacteria, including Bacillus licheniformis, Acinetobacter baumani, Escherichia coli, and Staphylococcus aureus.